Improving Essay Writing Skills with the Quantum Writer Learning Method in Facing the Destructive Era 4.0 - Syifa Alifia Fauziah; Septi Gumiandari (Publikasi Indonesia, 2024)
Learning essay writing skills is considered less interesting and boring for students so that students are less interested in learning essay writing skills. However, using interesting learning methods can be the solution. One of them is by using the quantum writer learning method. This research aims to improve students' learning of writing skills by using the quantum writer learning method for students. This research was conducted using literature review, by reading various articles, journals, and other publications related to the research topic. Article search is carried out using an accredited online database, namely Google Scholar. In the search for articles, the researcher limited the literature from 2014-2022. The keywords used are